Effectiveness of an educational session to sensitise the resident medical officers of a medical teaching institute in Mumbai towards cadaveric organ donation - Gupta, Priyanka; Bhate, Kamaxi (International Journal Of Community Medicine And Public Health, 2019)
Background: Resident medical officers play a critical role in facilitating conversion of potential deceased donors to actual donors. Since residency is the last opportunity for formal medical training, we contemplated deficiencies in knowledge might originate and a session of sensitization would disseminate updated information about organ donation. This study aims to assess the change in the knowledge and attitude of resident doctors towards organ donation after a programme of sensitization. Methods: A cross sectional study was conducted in March 2018 among newly inducted resident medical officers of KEM Hospital, Mumbai, after obtaining the institutional ethical approval and written informed consent. Using complete enumeration, 75 newly inducted resident doctors were approached out of which 49 consented to participate in the study. A self-administered questionnaire was used to assess the knowledge and perception before and after a programme of sensitization using a pre-test post-test study design. Results: Few numbers (18.36%) of resident doctors were aware of the various terminologies related to organ donation. There are lacunae in knowledge about difference between brainstem death, cardiac death and the organs that can be donated in each case. Moreover, participants who were initially unwilling to pledge for organ donation, were ready to pledge their organs post the sensitisation session (Z=-3.162, p=0.002). Conclusions: Participants knowledge improved over the programme of sensitization.